Quality of reporting of randomised controlled trials of herbal interventions in ASEAN Plus Six Countries: a systematic review. - Chayanin Pratoomsoot; Rosarin Sruamsiri; Piyameth Dilokthornsakul; Nathorn Chaiyakunapruk (PLoS ONE)
Background Many randomised controlled trials (RCTs) of herbal interventions have been conducted in the ASEAN Communities. Good quality reporting of RCTs is essential for assessing clinical significance. Given the importance ASEAN placed on herbal medicines, the reporting quality of RCTs of herbal interventions among the ASEAN Communities deserved a special attention. Objectives To systematically review the quality of reporting of RCTs of herbal interventions conducted in the ASEAN Plus Six Countries. Methods Searches were performed using PubMed, EMBASE, The Cochrane Library, and Allied and Complementary Medicine (AMED), from inception through October 2013. These were limited to studies specific to humans and RCTs. Herbal species search terms were based on those listed in the National List of Essential Medicines [NLEM (Thailand, 2011)]. Studies conducted in the ASEAN Plus Six Countries, published in English were included. Results Seventy-one articles were identified. Thirty (42.25%) RCTs were from ASEAN Countries, whereas 41 RCTs (57.75%) were from Plus Six Group. Adherence to the recommended CONSORT checklist items for reporting of RCTs of herbal interventions among ASEAN Plus Six Countries ranged from 0% to 97.18%. Less than a quarter of the RCTs (18.31%) reported information on standardisation of the herbal products. However, the scope of our interventions of interest was limited to those developed from 20 herbal species listed in the NLEM of Thailand. Conclusions The present study highlights the need to improve reporting quality of RCTs of herbal interventions across ASEAN Plus Six Communities.